(untitled) ("Journal "U". Economy. Management. Finance.", 2017)
In this article the author examines the prospects for logistics development of the air transport complexes in the Southern Federal district as the most priority directions of ensuring the stable and efficient operation of the transport system of the region, which finally leads to the advancement of the region in the market of international transit of goods.